(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article presents opinions and recommendations regarding the implementation, participation and implementation of legal relations by the employees of the internal affairs bodies, as well as the issues of raising their legal consciousness and legal culture in this regard.